Saving seed under international intellectual property Treaties and Iraqi Patent Law - Ali, Saman Abdulrahman (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
This study analyses legal position of saving seeds in internal and international levels, for example the TRIPS Agreement and the UPOV Convention of 1991. In this context the study attempts to compare and analyse the latest regulations of saving seeds in Iraq to previous amendments carried out by Coalition Provisional Authority (CPA) and previous Iraqi governments and to the TRIPS Agreement. The study finds out that the Law No. 15 of 2013 on Registration, Accreditation and Protection of Agricultural Varieties is an attempt to comply with the TRIPS Agreement by providing plant variety protection.